An empirical study of bureaucratic structural dimensions and their relationship to the variable organizational size. - Goodwin, John R. (University of Ottawa (Canada), 1978)
Although the organizational size literature has doubled in each five year period for the last twenty years, evidence on the effect and relationship of organizational size and organizational structure has been inconsistent and inconclusive. Do differences exist in organizational structure that reflect the differences in the size of the organization? The purpose of this study was to investigate the above question through examination of a set of homogeneous organizations. The organizational units investigated are the Ontario Colleges of Applied Arts and Technology. The general theoretical framework for the study was derived from Weber's bureaucratic theory (1947), the Aston group's contextual and structural variables (1968), and Reimann's framework of structural dimensions (1973). Based on this general framework, the study examined the relationship between organizational size and dimensions of organizational structure. In particular, the research investigated (a) the measures of size, (b) the size-structural relationship, (c) organizational size as determinant of organizational structure, and (d) the dimensionality of structure. As was predicted, a significant relationship existed between size and certain structural dimensions. Size was found to be positively related to specialization, delegation, vertical span, supervisory span (subordinate ratio), and was negatively related to centralization. A marked exception to the predicted relationship was the small negative correlation between size and formalization. A secondary question answered in this study has to do with the dimensionality of the structural variables. Principal component analysis indicated that the structural variables were reduceable to four independent structural dimensions. The multidimensional concept of structure was supported. Suggestions for further research included: (1) analysing the effect of structural adaptation to size on the overall effectiveness of the organization; (2) isolation of other of the contextual variables and studying their effect on structure; (3) relating organizational size, organizational complexity, and organizational structure; (4) relating organizational size, organizational differentiation and organizational structure; (5) a longitudinal study of organizational size and organizational structure in the Ontario colleges.
Keywords: Business Administration, Management.